Studies in the genus Hypericum L (Hypericaceae) 5(2). Sections 17. Hirtella to 19. Coridium - Robson, Norman K. B. (Phytotaxa, 2013)
Part 5(2) of this monographic series of papers on the genus Hypericum contains treatments of the remaining sections: Sections 17. Hirtella, 18. Taeniocarpium and 19. Coridium, which form a related group centred in eastern Turkey and Transcaucasia and extending in area from Morocco, Portugal and Ireland to western Xinjiang and the Altai and southern Angara-Sayan regions of Siberia. One new series, one new species and one new subspecies are described in Section 17. Hirtella (Series Scabra N.Robson, ser. nov., H. hedgei N.Robson, sp. nov., H. hyssopifolium subsp. acutum N.Robson, subsp. nov.), and two new species and one new subspecies in Section 18. Taeniocarpium (H. pseudorepens N.Robson, sp. nov., H. vaccinioides N.Robson, sp. nov., H. armenum subsp. iranicum N.Robson, subsp. nov.). Four new combinations or changes of rank are made, three in Section 17 (H. elongatum var. lythrifolium (Boiss.) N.Robson, comb. nov., H. elongatum var. racemosum (Kuntze) N.Robson, comb. nov., H. elongatum var. antasiaticum (Grossh.) N.Robson, stat. nov.) and one in Section 18: H. linarioides subsp. alpestre (Steven) N.Robson, stat. et comb. nov.